2022
DOI: 10.1242/dev.199974
|View full text |Cite
|
Sign up to set email alerts
|

A unique miR775-GALT9 module regulates leaf senescence in Arabidopsis during post-submergence recovery by modulating ethylene and the abscisic acid pathway

Abstract: Submergence-induced hypoxic condition negatively affects the plant growth and development, and causes early onset of senescence. Hypoxia alters the expression of a number of microRNAs (miRNAs). However, the molecular function of submergence stress-induced miRNAs in physiological or developmental changes and recovery remains poorly understood. Here we show that miR775 is an Arabidopsis thaliana-specific young and unique miRNA that possibly evolved non-canonically. miR775 post-transcriptionally regulates Galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Moreover, research has revealed that gma-miR172c influences the tolerance of soybean roots to stress by affecting the target gene NNC1 (Nodule Number Control 1) [44]. Many small RNAs have been experimentally confirmed to play a role in plant responses to abiotic stresses [5,[45][46][47][48]. NTP, as an enzyme that has the function of terminal modification, plays an important role in the process of sRNA biogenesis and degradation [8,23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research has revealed that gma-miR172c influences the tolerance of soybean roots to stress by affecting the target gene NNC1 (Nodule Number Control 1) [44]. Many small RNAs have been experimentally confirmed to play a role in plant responses to abiotic stresses [5,[45][46][47][48]. NTP, as an enzyme that has the function of terminal modification, plays an important role in the process of sRNA biogenesis and degradation [8,23].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin MT inhibits age-dependent and stress-induced leaf senescence in cucumber by activating the antioxidant system and the IAA synthesis and signaling pathway, while simultaneously inhibiting the ABA synthesis and signaling pathways, thereby reducing leaf senescence [99]. The miR775-GALT9 module regulates leaf senescence in Arabidopsis through crosstalk between the ethylene signaling and ABA biosynthetic pathways during post-submergence recovery [100].…”
Section: Agingmentioning
confidence: 99%
“…Previously, miRNAs have been implicated in various aspects of plant growth and development, including several abiotic and biotic stresses (Gautam et al, 2017, 2021; Mishra et al, 2022, 2023; Mishra & Maurya, 2023; Panda et al, 2022; Singh et al, 2018, 2020, 2021; Vivek & Kumar, 2021; Yadav et al, 2020). In animal systems, it is well known that miRNAs regulate the accumulation of serotonin by modulating various genes (Arai et al, 2013; Kassan et al, 2022; McKibben & Dwivedi, 2021; Zhao et al, 2019).…”
Section: Mirnas As Important Regulators Of Serotonin Biosynthesismentioning
confidence: 99%